Quantum‐mechanical condensed matter simulations with CRYSTAL. (4th March 2018) - Dovesi, Roberto; Erba, Alessandro; Orlando, Roberto; Zicovich‐Wilson, Claudio M.; Civalleri, Bartolomeo; Maschio, Lorenzo; Rérat, Michel; Casassa, Silvia; Baima, Jacopo; Salustro, Simone; Kirtman, Bernard
Abstract : The features of the publicly distributed CRYSTAL program for quantum‐mechanical condensed matter simulations are reviewed and the latest version of the code, namely CRYSTAL17, is introduced. Abstract : The latest release of the Crystal program for solid‐state quantum‐mechanical ab initio simulations is presented. The program adopts atom‐centered Gaussian‐type functions as a basis set, which makes it possible to perform all‐electron as well as pseudopotential calculations. Systems of any periodicity can be treated at the same level of accuracy (from 0D molecules, clusters and nanocrystals, to 1D polymers, helices, nanorods, and nanotubes, to 2D monolayers and slab models for surfaces, to actual 3D bulk crystals), without any artificial repetition along nonperiodic directions for 0–2D systems. Density functional theory calculations can be performed with a variety of functionals belonging to several classes: local‐density (LDA), generalized‐gradient (GGA), meta‐GGA, global hybrid, range‐separated hybrid, and self‐consistent system‐specific hybrid. In particular, hybrid functionals can be used at a modest computational cost, comparable to that of pure LDA and GGA formulations, because of the efficient implementation of exact nonlocal Fock exchange. Both translational and point‐symmetry features are fully exploited at all steps of the calculation, thus drastically reducing the corresponding computational cost. The various properties computed encompass electronic structure (including magnetic spin‐polarized open‐shell systems, electron density analysis), geometry (including full or constrained optimization, transition‐state search), vibrational properties (frequencies, infrared and Raman intensities, phonon density of states), thermal properties (quasi‐harmonic approximation), linear and nonlinear optical properties (static and dynamic [hyper]polarizabilities), strain properties (elasticity, piezoelectricity, photoelasticity), electron transport properties (Boltzmann, transport across nanojunctions), as well as X‐ray and inelastic neutron spectra. The program is distributed in serial, parallel, and massively parallel versions. In this paper, the original developments that have been devised and implemented in the last 4 years (since the distribution of the previous public version, Crystal14, occurred in December 2013) are described. This article is categorized under: Software > Quantum Chemistry Structure and Mechanism > Computational Materials Science Electronic Structure Theory > Density Functional Theory